Peningkatan Hasil Belajar Siswa dengan Metode Make a Match Pada Mata Pelajaran PAI di kelas V SD Negeri 2 Kamang - N, Welda (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve student learning outcomes on the topics of Q.S Ali Imran and Q.S Al Baqarah using the Make a Match learning method. The study was conducted in three cycles, where the first cycle showed unsatisfactory results with 58.33% completeness, while the second cycle improved to 66.67%. However, further improvements in the third cycle successfully increased completeness to 91.67%. The findings indicate that the Make a Match method can enhance student engagement, participation, and learning outcomes. Moreover, continuous reflection and improvements are crucial for achieving optimal results in the learning process.